Waste land [videorecording (DVD)] - Walker, Lucy; Jardim, João; Harley, Karen (Art House Films : Distributed in the U.S. by New Video, 2011)
Top-selling contemporary artist Vik Muniz takes viewers on an emotional journey to the world's largest landfill of the day, Jardim Gramacho. Here the catadores, who number in the thousands, work under the hot sun collecting recyclable materials such as bottles, plastic, and metal to be sold to wholesalers. Muniz invites the catadores to add refuse to his art, photographing the work from overhead. The finished artwork will then be on display in museums and auctions around the world.